2010
DOI: 10.1016/j.bbr.2009.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive recovery in the aged rat after stroke and anti-Nogo-A immunotherapy

Abstract: We have previously shown that immunotherapy directed against the protein Nogo-A leads to recovery on a skilled forelimb reaching task in rats after sensorimotor cortex stroke, which correlated with axonal and dendritic plasticity. Here we investigated anti-Nogo-A immunotherapy as an intervention to improve performance on a spatial memory task in aged rats after stroke, and whether cognitive recovery was correlated with structural plasticity. Aged rats underwent a unilateral distal permanent middle cerebral art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…Several studies showed that reducing expression of myelin-associated glycoprotein and Nogo-A may be a possible treatment to enhance cognitive recovery after brain injury. 33,34 For example, anti-Nogo-A immunotherapy improved performance in the water maze task after stroke with aged rats. 33 Morphological axonal or dendritic changes in the hippocampus or other brain areas may underlie the improved spatial memory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed that reducing expression of myelin-associated glycoprotein and Nogo-A may be a possible treatment to enhance cognitive recovery after brain injury. 33,34 For example, anti-Nogo-A immunotherapy improved performance in the water maze task after stroke with aged rats. 33 Morphological axonal or dendritic changes in the hippocampus or other brain areas may underlie the improved spatial memory.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 For example, anti-Nogo-A immunotherapy improved performance in the water maze task after stroke with aged rats. 33 Morphological axonal or dendritic changes in the hippocampus or other brain areas may underlie the improved spatial memory. 33 There are studies demonstrating that the efficacy of rehabilitative therapies after stroke is time dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of BMSC delivery, neurological improvements persisted in middle-aged rats (12 months) for at least one year [26]. Although neurological recovery was successful, dendritic and synaptic plasticity of hippocampal CA3 and CA1 pyramidal and dentate gyrus granule cells were not influenced by NogoA antibodies in aged (24 months) rats; yet improvements in spatial memory were present [73]. Indeed, the expression of plasticity-related proteins in neurons differs between young and old animals.…”
Section: Challenges For Neurorestorative Therapiesmentioning
confidence: 99%
“…Cerebral HIBD has been reported to impair memory because hippocampal neurons are susceptible to the deleterious effects of HI, and because the hippocampus is involved in the regulation of memory (Gillani et al, 2010). We found that NEP1-40 and fasudil resulted in a considerable reduction in HI-induced brain injury, when measured in the terms of the response capacity, food response and crawling.…”
Section: Discussionmentioning
confidence: 65%